2009
DOI: 10.1086/597292
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Hazards from Antimicrobial‐ResistantEscherichia coliof Animal Origin

Abstract: Because of the intensive use of antimicrobial agents in food animal production, meat is frequently contaminated with antimicrobial-resistant Escherichia coli. Humans can be colonized with E. coli of animal origin, and because of resistance to commonly used antimicrobial agents, these bacteria may cause infections for which limited therapeutic options are available. This may lead to treatment failure and can have serious consequences for the patient. Furthermore, E. coli of animal origin may act as a donor of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
182
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(187 citation statements)
references
References 38 publications
1
182
1
3
Order By: Relevance
“…Monitoring the distribution prevalence of tetracycline resistance genes, we found that the tetB gene had the highest frequency among the studied determinants. Escherichia coli is a facultative Gram-negative bacterium, which can cause many infections, like diarrhea, urinary tract infections, meningitis, peritonitis, and septicemia in humans (13). However, the most prevalent form of the extraintestinal infection caused by E. coli is urinary tract infection (14).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring the distribution prevalence of tetracycline resistance genes, we found that the tetB gene had the highest frequency among the studied determinants. Escherichia coli is a facultative Gram-negative bacterium, which can cause many infections, like diarrhea, urinary tract infections, meningitis, peritonitis, and septicemia in humans (13). However, the most prevalent form of the extraintestinal infection caused by E. coli is urinary tract infection (14).…”
Section: Discussionmentioning
confidence: 99%
“…The resistance was observed for Nilidixic Acid, Ciprofloxacin and Penicillin. The emergence of resistance to various antibiotics is of considerable medical and correlates, with their use and sometimes uncontrollably in the treatment of infectious diseases [1,[7][8][9]. In this situation raises new therapeutic molecules in the pharmaceutical industry with more power in less time and fewer adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…First, the colonization of zoophilic resistant bacteria in human gut could compromise the therapeutic effect of treatment of human infections because most antibiotics either are used both in humans and animals or share the same resistance mechanism. Second, there is the risk of gene exchange between colonized exogenous resistant bacteria and bacteria indigenous to human intestines (Hammerum & Heuer, 2009;Luangtongkum et al, 2009;Walsh & Fanning, 2008). Although it remains to be determined if colonization of pathogens of animal origin in human gut results in transfer of their resistant gene to human intestinal microbiome, the potential warrants careful examination in future studies.…”
Section: Impact Of Amr In Livestock Manure On the Development Of Amrmentioning
confidence: 99%